STUDI KOMPARASI KINERJA HULLFORM METODE FORMDATA DENGAN HULLFORM KAPAL KAYU TRADISIONAL TIPE BATANG - Zakki, Ahmad Fauzan; Manik, Parlindungan (Department of Naval Architecture - Diponegoro University, 2008)
At the moment most fisherman in Indonesia still use traditional fishing boat. this immeasurable Traditional ship its for. This matter earn us see almost in every coastal area region of Indonesia have form of desain different ship. Traditional Ship Desain represent result of study of nature, so that there no planning and calculation of standard desain before that ship is woke up but got skill by generations from all its predecessor. Because technical calculation of shipbuilding moment less is paid attention, hence in this research of comparison of performance of hull form among traditional ship of method of formdata. Available expecting of information so that can become an more beneficial alternative for the development of fishing boat hull form in territorial water of Batang. Marginally this research indicate that method ship hull form of formdata yield lower total resistance with difference 13,7%. At stability evaluation of hull method ship form of formdata have righting lever of larger ones. At excess navigation evaluation owned by except to traditional ship of movement of rolling